THE GAS INFLOW AND OUTFLOW RAIL IN STAR-FORMING GALAXIES AT z similar to 1.4 - Yabe, K; Ohta, K; Akiyama, M; Iwamuro, F; Tamura, N; Yuma, S; Dalton, G; Lewis, I (2015)
© 2015. The American Astronomical Society. All rights reserved.We try to constrain the gas inflow and outflow rate of star-forming galaxies at z ∼ 1.4 by employing a simple analytic model for the chemical evolution of galaxies. The sample is constructed based on a large near-infrared spectroscopic sample observed with Subaru/FMOS. The gas-phase metallicity is measured from the [N II] λ6584/Hα emission line ratio and the gas mass is derived from the extinction corrected Hα luminosity by assuming the Kennicutt-Schmidt law. We constrain the inflow and outflow rate from the least-χ 2 fittings of the observed gasmass fraction, stellar mass, and metallicity with the analytic model. The joint χ 2 fitting shows that the best-fit inflow rate is ∼1.8 and the outflow rate is ∼0.6 in units of star-formation rate. By applying the same analysis to the previous studies at z ∼ 0 and z ∼ 2.2, it is shown that both the inflow and outflow rates decrease with decreasing redshift, which implies the higher activity of gas flow process at higher redshift. The decreasing trend of the inflow rate from z ∼ 2.2 to z ∼ 0 agrees with that seen in previous observational works with different methods, though the absolute value is generally larger than in previous works. The outflow rate and its evolution from z ∼ 2.2 to z ∼ 0 obtained in this work agree well with the independent estimations in previous observational works.